Optimasi Sudut Pemasangan Panel Surya Bifasial di Indonesia dengan Metode Simulasi PVSyst - Ali, Mukhlis; Ludiana, Ludiana; Ramdani, Yogi (Fakultas Teknik UMSU, 2023)
PV rooftop is a renewable energy which becomes Indonesian government priority to implement in the residential and commercial buildings. However, its implementation faces a big challenge from Indonesian climate which mostly cloudy and rainy. This threat makes increasing in PV rooftop capacity, though the available rooftop area is limited. So, there is a requirement to increase the efficiency or energy output from PV rooftop. A solution which can potentially implement to do that is the use of PV bifacial. In some previous researches, PV bifacial can increase energy output of PV rooftop about 2%-12% compares to PV monofacial. However, the value of energy output from PV bifacial depends on tilt angle of PV. Tilt angle is a factor which related to latitude position of a location. Due to the most previous researches about PV bifacial are in subtropical countries, so there is a necessity to find an optimum tilt angle for PV bifacial in Indonesia. The purpose of this research is to find an optimum tilt angle and energy output of PV bifacial in several places in Indonesia. This research is a basic research so it will use simulation method using PVSyst software. PVSyst software is prominent software in PV design simulation which is already used in some previous researches. This research concludes that PV bifacial has 1o-2o optimum tilt angle difference compares to PV monofacial. The use of PV bifacial also can increase energy output 2.25%-3,5% better than PV monofacial.